Entrepreneurial families in business across generations, contexts and cultures - James, Albert E.; Hadjielias, Elias; Guerrero, Maribel; Discua Cruz, Allan Fernando; Basco, Rodrigo (My University, 2020)
Purpose: This article is the editorial for the special issue on “Entrepreneurial Families in Business Across Generations, Contexts and Cultures”. We aim to develop a road map that can help academics and practitioners navigate the findings of the articles contained in this special issue. We also suggest future lines of research around the topic of entrepreneurial families in business. Design/methodology/approach: We develop a conceptual model for interpreting and understanding entrepreneurial families in business across contexts and time. Findings: Our conceptual model highlights the importance of context and time when conducting research on entrepreneurial families in business. Practical implications: The findings in this special issue will be of relevance for decision makers who tailor policies that embrace different economic and social actors, including entrepreneurial families. Originality/value: This editorial and the articles that make up this special issue contribute to family business research by contextualising the phenomenon of entrepreneurial families in business. We propose a new holistic perspective to incorporate context and time in the study of entrepreneurial families that own, govern and manage family firms over time.
Keywords: Contexts; Cultures; Entrepreneurial families; Family; Family business; Generational cohorts